Noisy Prices and Inference Regarding Returns. (7th March 2013) - ASPAROUHOVA, ELENA; BESSEMBINDER, HENDRIK; KALCHEVA, IVALINA
ABSTRACT Temporary deviations of trade prices from fundamental values impart bias to estimates of mean returns to individual securities, to differences in mean returns across portfolios, and to parameters estimated in return regressions. We consider a number of corrections, and show them to be effective under reasonable assumptions. In an application to the Center for Research in Security Prices monthly returns, the corrections indicate significant biases in uncorrected return premium estimates associated with an array of firm characteristics. The bias can be large in economic terms, for example, equal to 50% or more of the corrected estimate for firm size and share price.